1984
DOI: 10.1111/j.1745-6584.1984.tb01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence Near Oil and Gas Fields, Houston, Texasa

Abstract: Subsidence profiles across 29 oil and gas fields in the 12,200‐km2 Houston, Texas, regional subsidence area, which is caused by decline of ground‐water level, suggest that the contribution of petroleum withdrawal to local land subsidence is small. Despite large volumes of petroleum production, subsidence at most fields was not increased by oil and gas withdrawal. Local increases of subsidence were detected at only six fields—Alco‐Mag, Chocolate Bayou, Goose Creek, Hastings, Mykawa, and South Houston. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…1) (Pratt and Johnson, 1926). Although subsidence was first identified in the Houston-Galveston region as a result of hydrocarbon extraction at this particular oil field, most of the subsidence in the Houston-Galveston region is a direct result of groundwater withdrawals that have depressured and dewatered the Chicot and Evangeline aquifers, thereby causing compaction of the aquifer sediments (Winslow and Doyel, 1954;Winslow and Wood, 1959;Gabrysch and Bonnet, 1975;Gabrysch, 1984;Holzer and Bluntzer, 1984;Kasmarek, Gabrysch, and Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1) (Pratt and Johnson, 1926). Although subsidence was first identified in the Houston-Galveston region as a result of hydrocarbon extraction at this particular oil field, most of the subsidence in the Houston-Galveston region is a direct result of groundwater withdrawals that have depressured and dewatered the Chicot and Evangeline aquifers, thereby causing compaction of the aquifer sediments (Winslow and Doyel, 1954;Winslow and Wood, 1959;Gabrysch and Bonnet, 1975;Gabrysch, 1984;Holzer and Bluntzer, 1984;Kasmarek, Gabrysch, and Johnson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Four factors have been frequently mentioned in the literature, including geological factors, such as consolidation of Holocene sediments, lithospheric flexure response to sediment loadings, tectonic movements on growth faults and anthropogenic factors, mostly human-induced fluid extraction and hydrocarbon production [20][21][22][23][24]. Yuill et al (2009) found that the range of rates caused by the four factors were 1.0-8.0, 1.0-5.0, 0.1-20 and 0-3 mm/year [9].…”
Section: Study Areamentioning
confidence: 99%
“…The Wooster Fault located on the north end of the Goose Creek Field along with the Hogg Island Fault on the south end of the Goose Creek Field form an east-west graben in which the oil field is located (Sheets, 1979). Faulting may be associated with subsidence caused by production of the Goose Creek Field during 1917-25 (Holzer and Bluntzer, 1984).…”
Section: Satsumamentioning
confidence: 99%
“…Secondly, acquisition of data, such as bottom hole pressures involved in petroleum production, is difficult. Previous studies within the Harris-Galveston region have focused on the Chocolate Bayou, Mykawa, South Houston, and the Goose Creek Fields (Gabrysch and Coplin, 1990;Holzer and Bluntzer, 1984;Kreitler, 1976;Yerkes and Castle, 1969). Holzer and Bluntzer (1984) show that the majority of the subsidence historically in the Houston area can be attributed to groundwater withdrawal with the exception of the Barbers Hill, Cedar Bayou, Humble and Pierce Junction Fields.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 1 more Smart Citation